Pengaruh Reksadana Syariah, Saham Syariah, dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia - Amelia, Reza Ariessa Rizka; Budiman, Septian Arief (Pusat P2M Politeknik Negeri Batam, 2023)
This research aims to prove empirically the influence of Sharia Mutual Funds, Sharia Stocks and Inflation onEconomic Growth in Indonesia with Sharia Bank Size as a Moderating Variable. The type of research used isquantitative. The type of data used is secondary data in the form of Consumer Price Index reports registeredwith the Central Statistics Agency (BPS), reports on Sharia Mutual Funds and Sharia Shares registered withthe Financial Services Authority (OJK), as well as Inflation reports registered with Bank Indonesia for theperiod January 2018 - December 2022. This research uses a saturated sample with a purposive samplingmethod. Data processing using the Microsoft Office Excel 2010 Program and the Eviews 9 Statistics Program.The research results show that Sharia Mutual Funds, Sharia Stocks and Inflation simultaneously influenceeconomic growth in Indonesia. Partially, Sharia Mutual Funds, Sharia Stocks and Inflation influence EconomicGrowth in Indonesia.